ANALISIS KADAR PROTEIN DAN LEMAK PADA IKAN JULUNG-JULUNG ASAP (Hemiramphus far) ASAL KECAMATAN KAYOA MALUKU UTARA DENGAN METODE KJELDAHL DAN GRAVIMETRI - Mamat Pratama; Muzakkir Baits; Nurul Auliah A.R. Saman (As-Syifaa Jurnal Farmasi, 2014)
Content Analysis of Protein And Fats In fish smoked julung-julung (Hemiramphus far) Origin of North Maluku, Subdistrict Kayoa with Kjeldahl Method and Gravimetri Method. An investigation of analysis of protein and fat content in fish smoked julung-julung (Hemiramphus far) Origin Of North Maluku,District kayoa with kjeldahl method and gravimetri method. This study aimed to obtain scientific data about the content of protein and fat in fish smoked julung-julung (Hemiramphus far).This includes research on the protein nitrogen content of the test by Kjeldahl Method and analysis of fat content by using the method showed that the levels Gravimetri. The result showed that the samples of smoked fish fated to be unlucky-fated to unlucky (Hemiramphus far) obtained A water content of 13,90%, protein content of 71,03% and fat content 4,13% and in fish simple fated to be unlucky-fated to unlucky (Hemiramphus far) obtained B water content of 14,07%, protein content of 71,67% and fat content 5,38%.Keywords : Smoked fish julung-julung, protein, fat, kjeldahl and gravimetri.